1997
DOI: 10.1097/00000658-199706000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Trial Comparing Ileal Pouch-Anal Anastomosis Performed by Excising the Anal Mucosa to Ileal Pouch-Anal Anastomosis Performed by Preserving the Anal Mucosa

Abstract: ObjectiveThe purpose of the study is to compare the results of ileal pouch-anal anastomosis (IPM) in patients in whom the anal mucosa is excised by handsewn techniques to those in whom the mucosa is preserved using stapling techniques. Summary Background DataIleal pouch-anal anastomosis is the operation of choice for patients with chronic ulcerative colitis requiring proctocolectomy. Controversy exists over whether preserving the transitional mucosa of the anal canal improves outcomes. MethodsForty-one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(82 citation statements)
references
References 37 publications
5
77
0
Order By: Relevance
“…Previous studies reported better fecal continence after stapled IPAA without mucosectomy compared with hand‐sewn IPAA with mucosectomy, possibly as a result of reduced anal canal manipulation and preservation of ATZ 5, 7, 8, 9, 10. In contrast, the studies by Remzi et al.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Previous studies reported better fecal continence after stapled IPAA without mucosectomy compared with hand‐sewn IPAA with mucosectomy, possibly as a result of reduced anal canal manipulation and preservation of ATZ 5, 7, 8, 9, 10. In contrast, the studies by Remzi et al.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have reported several pros and cons on these two anastomotic techniques. Stapled IPAA is the simpler type of anastomosis with shorter length of operation and better fecal continence possibly as a result of omission of mucosectomy and preservation of the anal transitional zone (ATZ) 5, 7, 8, 9, 10. In contrast, hand‐sewn IPAA with mucosectomy can reduce a substantial risk for developing adenomas at the anastomotic site 11…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,16,20 Various studies have even shown these variations to be influencing factors for PRSC. 12,30,31 Our study design provided several advantages. Data about the preclinical status and data obtained from direct contact with the patients at each of the follow-up consultations were entered into a clinical registry and documented prospectively.…”
Section: Discussionmentioning
confidence: 99%